Two Recent Massive Breeding Failures in an Adélie Penguin Colony Call for the Creation of a Marine Protected Area in D'Urville Sea/Mertz - Ropert-Coudert, Yan; Kato, Akiko; Shiomi, Kozue; Barbraud, Christophe; Angelier, Frédéric; Delord, Karine; Poupart, Timothée; Koubbi, Philippe; Raclot, Thierry (Frontiers in Marine Science, 2018)
In the d’Urville Sea in East Antarctica, a population of roughly 20,000 pairs of Adélie penguins of Iles des Pétrels (Terre Adélie) has experienced two massive breeding failures, with no chick surviving the 2013-14 and 2015-16 breeding seasons. In both seasons the extent of sea ice in front of the colony persisted throughout the breeding cycle of the birds. The timing of sea-ice recession differed greatly between seasons and the absence of polynya in a crucial phase of the cycle were paramount in driving these failures. The change in the icescape in front of Ile des Pétrels following the calving of the Mertz glacier in 2010, together with increase in precipitations and changes in sea-ice firmness explain this situation and are discussed in the present manuscript. To prevent additional future impacts on this colony, like competition with fisheries for instance, we strongly support a scientific research zone in the d'Urville Sea – Mertz area, one of the three zones of proposed Marine Protected Area in East Antarctica to the Commission for the Conservation of Antarctic Marine Living Resources.